Cadherins orchestrate specific patterns of perisomatic inhibition onto distinct pyramidal cell populations - Julie Jézéquel; Giuseppe Condomitti; Tim Kroon; Fursham Hamid; Stella Sanalidou; Teresa Garcés; Patricia Maeso; Maddalena Balia; Zhaohui Hu; Setsuko Sahara; Beatriz Rico (Nature Communications)
Abstract GABAergic interneurons were thought to regulate excitatory networks by establishing unselective connections onto diverse pyramidal cell populations, but recent studies demonstrate the existence of a cell type-specific inhibitory connectome. How and when interneurons establish precise connectivity patterns among intermingled populations of excitatory neurons remains enigmatic. We explore the molecular mechanisms orchestrating the emergence of cell type-specific inhibition in the mouse cerebral cortex. We demonstrate that layer 5 intra- (L5 IT) and extra-telencephalic (L5 ET) neurons express unique transcriptional programs, allowing them to shape parvalbumin- (PV+) and cholecystokinin-positive (CCK+) interneuron wiring. We identified Cdh12 and Cdh13, two cadherin superfamily members, as underpinnings of cell type- and input-specific inhibitory patterns of L5 pyramidal cell populations. Multiplex monosynaptic tracing revealed a minimal overlap between IT and ET presynaptic inhibitory networks and suggests that different PV+ basket cell populations innervate distinct L5 pyramidal cell types. Here, we unravel the contribution of cadherins in shaping cell-type-specific cortical interneuron wiring.